Proceedings of the 5th International Conference on Frontiers in Intelligent Computing: Theory and Applications FICTA 2016, Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Udgata, Siba K.; Pattnaik, Prasant Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book is a collection of high-quality peer-reviewed research papers presented at International Conference on Frontiers of Intelligent Computing: Theory and applications (FICTA 2016) held at School of Computer Engineering, KIIT University, Bhubaneswar, India during 16 - 17 September 2016. The book aims to present theories, methodologies, new ideas, experiences, applications in all areas of intelligent computing and its applications to various engineering disciplines like computer science, electronics, electrical, mechanical engineering, etc.
Chapter 1. Cloud Computing Technology as an Auto Filtration System for Cost Reduction while Roaming -- Chapter 2. A Secured Digital Signature Using Conjugacy and DLP on Non-Commutative Group over Finite Field -- Chapter 3. Design of Visual Cryptography Scheme Using C(m,w) Combinations -- Chapter 4. Some Properties of Rough Sets on Fuzzy Approximation Spaces and Applications -- Chapter 5. Join Operations to Enhance Performance in Hadoop MapReduce Environment -- Chapter 6. Multipath Load Balancing and Secure Adaptive Routing Protocol for Service Oriented WSNs -- Chapter 7. Visual Based Information Retrieval Using Voronoi Tree -- Chapter 8. EEG Based Oscitancy Classification System for Accidental Prevention -- Chapter 9. Low Power 14T Hybrid Full Adder Cell -- Chapter 10. A Combined System for Regionalization in Spatial Data Mining Based on Fuzzy C- Means Algorithm with Gravitational Search Algorithm -- Chapter 11. Adaptive Spatio-Temporal Filtering with Motion Estimation for Mixed Noise Removal and Contrast Enhancement in Video Sequence -- Chapter 12. Improved Dynamic Time Warping Based Approach for Activity Recognition -- Chapter 13. Design & Functional Verification of Axi2Ocp Bridge for Highly Optimized Bus Utilization and Closure Using Functional Coverage -- Chapter 14. STRIDE Based Analysis of the Chrome Browser Extensions API -- Chapter 15. Social and Temporal-Aware Personalized Recommendation for Best Spreaders on Information Sharing -- Chapter 16. Person Recognition Using Surf Features and Vola-Jones Algorithm -- Chapter 17. A Novel Representation for Classification of User Sentiments -- Chapter 18. Information Retrieval for Gujarati Language Using Cosine Similarity Based Vector Space Model -- Chapter 19. Design and Optimization of Fractal Antenna for UWB Application -- Chapter 20. Multi-objective IT Professionals' Utilization ProblemsUsing Fuzzy Goal Programming -- Chapter 21. An Innovative Method for Load Balanced Clustering Problem for Wireless Sensor Network in Mobile Cloud Computing -- Chapter 22. BLDC Motor Drive with Power Factor Correction Using PWM Rectifier -- Chapter 23. A 3D Approach for Palm Leaf Character Recognition Using Histogram Computation and Distance Profile Features -- Chapter 24. Gradient Magnitude Based Watershed Segmentation for Brain Tumor Segmentation and Classification -- Chapter 25. A Novel Edge Based Chaotic Steganography Method Using Neural Network -- Chapter 26. PLoc-Euk: An Ensemble Classifier for Prediction of Eukaryotic Protein Sub-Cellular Localization -- Chapter 27. Feature Optimization to Recognize Telugu Handwritten Characters by Implementing DE and PSO Techniques -- Chapter 28. Dengue Fever Classification Using Gene Expression Data: A PSO Based Artificial Neural Network Approach -- Chapter 29. L-Slotted Microstrip Fed Monopole Antenna for Triple Band WLAN and WiMAX Applications -- Chapter 30. Modified Non Linear Diffusion Approach for Multiplicative Noise -- Chapter 31. Performance Analysis of Fully Depleted SOI Tapered Body Reduced Source (FD-SOI TBRS) MOSFET for Low Power Digital Applications -- Chapter 32. A Latest Comprehensive Study on Structured Threat Information Expression (STIX) and Trusted Automated Exchange of Indicator Information (TAXII) -- Chapter 33. Robust Flare Phase Auto Landing of Aircrafts, Based on Modified ASBO -- Chapter 34. Drive-by-Download Malware Detection in Hosts by Analyzing System Resource Utilization Using One Class Support Vector Machines -- Chapter 35. 2D Shape Representation and Analysis Using Edge Histogram and Shape Feature -- Chapter 36. A Study & Analysis of Different Brain Tumor Segmentation Techniques -- Chapter 37. Threshold Based Clustering Algorithm Analyzes Diabetic Mellitus -- Chapter 38. Automatic Classification of Lung Nodules into Benign or Malignant Using SVM Classifier -- Chapter 39. RSentiment: A Tool to Extract Meaningful Insights from Textual Reviews -- Chapter 40. Preventive Maintenance Approach for Storage and Retrieval of Sensitive Data -- Chapter 41. Domain Independent Approach for Aspect Oriented Sentiment Analysis for Product Reviews -- Chapter 42. Privacy Preserving Data Mining: A Parametric Analysis -- Chapter 43. Approach for Emotion Extraction from Text -- Chapter 44. Bio-inspired Algorithms for Mobile Location Management - A New Paradigm -- Chapter 45. Automatic Detection of Diabetic Retinopathy Using Two Phase Top-hat Transformations - A Novel Approach -- Chapter 46. Evaluation of Heart Rate Using Reflectance of An Image -- Chapter 47. Analysis of Logs by Using Logstash -- Chapter 48. Performance of Multiple String Matching Algorithms in Text Mining -- Chapter 49. Estimation of Degree of Connectivity to Predict Quality of Software Design -- Chapter 50. Information Retrieval through the Web and Semantic Knowledge-Driven Automatic Question Answering System -- Chapter 51. Level Set Based Liver Segmentation and Classification by SVM -- Chapter 52. A Purely Localized Random Key Sequencing Using Accelerated Hashing in Wireless Ad-hoc Networks -- Chapter 53. GOASREP: Goal Oriented Approach for Software Requirements Elicitation and Prioritization Using Analytic Hierarchy Process -- Chapter 54. Confidentiality and Storage of Data in Cloud Environment -- Chapter 55. An Exploratory Study of RDF: A Data Model for Cloud Computing -- Chapter 56. Optimization of Overcurrent Relays in Microgrid Using Interior Point Method and Active Set Method -- Chapter 57. Series Smart Wire - Managing Load and Congestion in Transmission Line -- Chapter 58. Recognizing Human Faces with Tilt -- Chapter 59. Word-Level Script Identification from Scene Images -- Chapter 60. Writer Specific Parameters for Online Signature Verification -- Chapter 61. Gene Ontology Based Function Prediction of Human Protein Using Protein Sequence and Neighborhood Property of PPI Network -- Chapter 62. TKAR: Efficient Mining of Top - k Association Rules on Real - Life Datasets -- Chapter 63. Predicting Defect of Software System -- Chapter 64. Fusion of Medical Image Using STSVD -- Chapter 65. Modified Cuckoo Search Algorithm for Fittest Relay Identification in Microgrid -- Chapter 66. A Method for the Selection of Agile Methods Using AHP -- Chapter 67. Load Balancing with Job Switching in Cloud Computing Network -- Chapter 68. An Efficient Detection and Mitigation of Selfish and Black Hole Attack in Cognitive Mobile Ad-hoc Network -- Chapter 69. Cryptanalysis of Secure Routing among Authenticated Nodes in MANETs -- Chapter 70. Novel Techniques for Detection of Anomalies in Brain MR Images.-Chapter 71. Convex Hyperspectral Unmixing Algorithm Using Parameterized Non-Convex Penalty Function.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems